Research on global citizenship education in Asia : conceptions, perceptions, and practice - Alviar-Martin, Theresa; Baildon, Mark (Research in social education., 2020)
"This edited book provides new research highlighting philosophical traditions, emerging perceptions, and the situated practice of global citizenship education (GCE) in Asian societies. The book includes chapters that provide: 1) conceptions and frameworks of GCE in Asian societies; 2) analyses of contexts, policies, and curricula that influence GCE reform efforts in Asia; and 3) studies of students' and teachers' experiences of GCE in schools in different Asian contexts. While much citizenship education has focused on constructions and enactments of GCE in Western societies, this volume re-centers investigations of GCE amid Asian contexts, identities, and practices. In doing so, the contributors to this volume give voice to scholarship grounded in Asia, and the book provides a platform for sharing different approaches, strategies, and research across Asian societies. As nations grapple with how to prepare young citizens to face issues confronting our world, this book expands visions of how GCE might be conceptualized, contextualized, and taught; and how innovative curriculum initiatives and pedagogies can be developed and enacted"--